2007
DOI: 10.1016/j.susc.2007.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of an InxGa1−xN/GaN nanostructure

Abstract: The structural and optical properties of an In x Ga 1Àx N/GaN multi-quantum well (MQW) were investigated by using X-ray diffraction (XRD), atomic force microscopy (AFM), spectroscopic ellipsometry (SE) and photoluminescence (PL). The MQW structure was grown on c-plane (0 0 0 1)-faced sapphire substrates in a low pressure metalorganic chemical vapor deposition (MOCVD) reactor. The room temperature photoluminescence spectrum exhibited a blue emission at 2.84 eV and a much weaker and broader yellow emission band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…2. The layer thicknesses and In content were measured by X-ray reflectivity and high resolution X-ray techniques in previous study [12]. At x = 0.096 value, a strong blue emission at 2.86 eV from photoluminescence spectrum is observed as shown in ref.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…2. The layer thicknesses and In content were measured by X-ray reflectivity and high resolution X-ray techniques in previous study [12]. At x = 0.096 value, a strong blue emission at 2.86 eV from photoluminescence spectrum is observed as shown in ref.…”
Section: Methodsmentioning
confidence: 93%
“…At x = 0.096 value, a strong blue emission at 2.86 eV from photoluminescence spectrum is observed as shown in ref. [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the growing parameters, surface dynamics and lattice structures are of significant importance for the development of nitride based optoelectronic and microelectronic devices. The temperature has a critical importance due to its effect on the lattice structures and the modification of the band range [12]. However, the studies performed with regards to the effect of temperature on the device performance are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Edge and mixed (screw/edge) dislocations in nitride materials act as nonradiative recombination centers and as conduits for charge transport resulting in leakage currents and breakdown (Amano et al, 2003;Davis et al, 2002). While high threading dislocation density is acceptable for light emitting diodes (LEDs) 6 -usually their small effect on the performance is attributed to the potential fluctuations related to the indium composition fluctuations (resulting from the poor In incorporation in the epitaxial layer during the growth or from the phase separation due to the large miscibility gap (I-hsiu & Stringfellow, 1996;Karpov, 1998;Korcak et al, 2007) ) observed in the active layers made from the ternary solid solution InGaN and in the corresponding QWs (Christen et al, 2003;Limb, 2007;Mukai et al, 2001) that provide the localization of carriers and reduce their in-plane diffusion to the non-radiative recombination centers -the high dislocation density, however, is fatal for laser diodes and power transistors; even for the LEDs including indium-free violet ones (Usikov et al, 2003) it leads to the drop in the efficiency and is the main factor of the device failure (Karpov, 2009;Roycroft et al, 2004 (Jain et al, 2000;Kukushkin et al, 2008;Miskys et al, 2003). Sapphire is a good choice for the nitride layers from the crystallographic point of view: crystal orientations of sapphire and gallium nitride grown on c-plane (0001) are parallel, with the unit cell of GaN being rotated by 30 • about c axis with respect to the unit cell of sapphire; the (1100) axis of GaN is parallel to the (1210) sapphire axis (Jain et al, 2000).…”
mentioning
confidence: 99%